Water and sediment quality of urban water bodies in cold climates - Rentz, Ralf (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2011)
The aim of this study was to investigate and quantify pollution impact on urban waterbodies in cold climates and to find out which complex processes and influencing factors causetrapping or spread of pollutants. In order to do that water, sediment and porewater samplesfrom bays and stormwater ditches in Luleå, northern Sweden, and from an artificialstormwater pond in Sollentuna, south-central Sweden, were analysed for LOI, trace metalsand PAHs. For surface water the particular, colloidal and truly dissolved elementconcentrations were determined by membrane filtration (0.22 μm pore size, 142 mmdiameter, Millipore® mixed cellulose esters) and ultrafiltration in a Millipore® Prep/Scalesystem (manufacturer specified cut-off of 1 kDa and a filter membrane area of 0.54 m2).Sediment and porewater samples from bays in Luleå, receiving stormwater discharge,showed enrichment of Cd, Cu, Pb and Zn. Also the PAH content was enriched, in particularfor phenantrene, anthracene, fluoranthene and pyrene. Water volume and turnover rate in thewater bodies with low or no surface runoff during wintertime, and ice covering, contribute toanoxic conditions in the water column and sediments. The enclosure of the bay Skutviken in1962 illustrates for how reduced water circulation promotes the occurrence of anoxicconditions with sulphate reduction. As a consequence of these conditions, metals are trappedin the sediments as sulphides. The use of trace metal ratios could not indicate road runoff asmain source for sediment pollution. The degree of pollution was higher in the sediments ofthe bays in Luleå than in a 1998 implemented, stormwater pond in Sollentuna, which receiveshighway runoff.Water concentrations of Cd, Co, Cr, Cu, Fe, Mn, Na, Ni, Pb, S, and Zn showed seasonalvariations in Sollentuna. In winter de-icing agents and use of studded tires cause higher metalconcentrations of Co, Cr, Cu, Ni, Mn, Na, and Zn dominated by the truly dissolved phase. InLuleå depletion of oxygen under the thick ice cover can change the redox border from ...